La sátira de costumbres como artefacto ideológico. En torno a un opúsculo de 1808 - Claude Morange (Cahiers de Civilisation Espagnole Contemporaine)
The invasion of Spain by France in 1808 was followed by the diffusion of many pamphlets and press articles. Among this extensive literature, a brochure entitled Higiene política de la España is worth mentioning: it has not drawn much attention from the commentators probably because it is a literary composition of a poor quality, but it exemplifies in a tellingly manner the political methods that the conservatives used to resort to in order to foster a reading of patriotic resistance that would fit into their ideological frame of interpretation. Amalgamating facts and ideas in an unsubtle manner, the author of this volume indeed conceptualises the French invasion as the unavoidable consequence of the forgetting of their fundamental values by the Spaniards and as the result of another earlier “invasion”: the diffusion into Spain of ways of life and customs that came from beyond the Pyrenees. The author therefore calls his compatriots to take action and reject political domination, moral corruption, and ideological subversion. This reminds us, if we ever needed being reminded, that in 1808, patriotic uprising was not always synonymous with political revolution.